1978
DOI: 10.1302/0301-620x.60b2.659473
|View full text |Cite
|
Sign up to set email alerts
|

Experimental production of forward dislocation in the human cervical spine

Abstract: Entire human cadaveric cervical spines with the basiocciput were subjected to load in a compression apparatus to simulate the clinical situation of forward dislocation. The movements were recorded by lateral cineradiography. Vertical load was measured by a potentiometric transmitter synchronised with each frame of the cineradiograph. The lower part of the spine was flexed and fixed, and the upper extended and free to move forward. Vertical compression then produced bilateral dislocation of the facets without f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 6 publications
3
35
0
Order By: Relevance
“…There exist few biomechanical studies of BFD with which our results may be compared, with most being limited by unrealistic quasi-static loading or manual ligament transection [3,4,24]. These previous models have been used to determine ligament injuries, investigate loading directions responsible for BFD, and to study vertebral artery occlusion [26] and stabilization techniques [9,16,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist few biomechanical studies of BFD with which our results may be compared, with most being limited by unrealistic quasi-static loading or manual ligament transection [3,4,24]. These previous models have been used to determine ligament injuries, investigate loading directions responsible for BFD, and to study vertebral artery occlusion [26] and stabilization techniques [9,16,27].…”
Section: Discussionmentioning
confidence: 99%
“…Beatson [4] created dislocations using whole cervical spine specimens, and reported ruptures of the interspinous, capsular, and posterior longitudinal ligaments and annular fibers, though neither the high speed loading nor motion patterns were reported. Bauze and Ardran [3] applied flexion and compression loading to whole cervical spine specimens that were immobilized inferior to C5/6 to cause BFD at this spinal level. Interspinous, capsular, and anterior longitudinal ligament injuries were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral facet dislocation was most common at the C6-7 level and unilateral facet dislocation at the C5-6 level in their series. Axial rotation exists in unilateral facet dislocation [1]. Maiman et al [9] described 28 patients with bilateral facet dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common levels were C5-6 and C6-7, having ten each (total 71.4%). Bilateral facet dislocation is associated with significant soft tissue injury, including rupture of the posterior ligamentous complex, facet joint capsules, annulus fibrosus, and usually the anterior and posterior longitudinal ligaments [1,2,4,16] with both facets remaining intact but dislocated. The inferior facet of the upper vertebra slides over the tip of the superior facet of the lower vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of players being of equal standard in the front row of the scrum, particularly at schoolboy level, has been appreciated. 9 The detection by means of a MRI of narrowing of the cervical vertebral canal and the detection of undue mobility of vertebrae has shown latterly the import ance of minor degrees of injury to the discs. 10 Now a rugby player who has sustained an injury to his skull resulting in a painful neck without neurological in volvement can have a scan performed and it has been frequently shown that there is damage to the disc which puts the player at risk if he carries on playing rugby.…”
Section: Summary Of the Researchmentioning
confidence: 99%